2008
DOI: 10.1021/jp801865s
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of Atactic Polystyrene: Linear Energy Transfer Effects

Abstract: Atactic glassy polystyrene (PS) has been irradiated in anoxic conditions by electron and ion beams. The induced modifications were followed, in situ, by Fourier transform infrared spectroscopy (FTIR). In-film modifications and hydrocarbon gas release were followed. In-situ measurements allowed one to avoid any spurious oxidation of the films after irradiation and also permitted studying in detail the evolution with dose of the FTIR spectra. The data were quantitatively analyzed, and we present a complete analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…This result is similar to results obtained on our previous work: when LET increases, i.e. when excitation and ionization density increases, the radiation protection given by the benzene ring is lost [25].…”
Section: Low Dose Rangesupporting
confidence: 92%
See 1 more Smart Citation
“…This result is similar to results obtained on our previous work: when LET increases, i.e. when excitation and ionization density increases, the radiation protection given by the benzene ring is lost [25].…”
Section: Low Dose Rangesupporting
confidence: 92%
“…Results obtained when irradiating polystyrene, PS, could give some insight on the chemical modifications presumably induced in the aromatic moiety of PES. The major modifications observed in irradiated PS are trans-vinylenes, vinylidenes, benzene and alkynes [25]. Vinyl creation cannot be ruled out [26] but this group is likely formed at a much lower yield.…”
Section: Vinylsmentioning
confidence: 99%
“…5). This compares well, for instance, with the quadratic dependence of damage cross sections on stopping power in poly(p-phenylene sulfide) (PPS), which is independent on the chemical nature of the bonds [26]. This non-linearity implies that the dose from which the IBIL of BC-400 starts deteriorating is variable and depends on the stopping power of the particles.…”
Section: Methodssupporting
confidence: 53%
“…In our previous work focused on the effect of ester bonds position effect in methylene containing polymers, we have observed that in-chain defects are substantially more efficient that defects position on side-chains [6]. The second hypothesis comes from the fact that the radiation protection effects of protective bonds are diminished when LET is increasing [3,4,26]. It might be concluded that even at low LET, vinyl bonds are less effective than in-chain double bonds to protect polyethylene.…”
Section: Let Effectmentioning
confidence: 99%
“…Regardless of the position of the energy sink, it has been shown by Chang and LaVerne [4] and by Ferry et al [26] that increasing LET induces a loss of radiation protection efficiency, which implies a loss of energy and radical migration. As on side-chains, energy transfers are already drastically reduced compared to in-chains migration under low LET ionizing rays, it can probably be supposed that their protection efficiency will be lost at a LET lower than the one needed to lose the protection induced from in-chains defects.…”
Section: Let Effectmentioning
confidence: 99%